Effect of parasitic isopods in the marine fish Carangids malabaricus off Parangipettai coastal waters. (19th April 2010) - Ravichandran, S.; Sunitha, S.; Rameshkumar, G.
The effect of parasitic isopods on the fish Carangids malabaricus was studied. The reduction in gill raker count and gill surface area was observed as a function of infestation. The maximum reduction in respiratory surface area was observed in the first gill arch and the minimum in the third gill arch. Infested fish had extremely pale gills, indicating severe anaemia. Gill rakers were seriously lost, apical edges damaged and out off gill lamellae heavily destroyed. Some secondary gill lamellae were fused or thickened. Between the gill lamellae, callus-like thickening was observed. The histopathological symptoms owing to isopod parasites (Joryma tartoor) were categorised as gross lesions and histopathological anomalies noticed in the present study.